C1 Metabolism Inhibition and Nitrogen Deprivation Trigger Triacylglycerol Accumulation in Arabidopsis thaliana Cell Cultures and Highlight a Role of NPC in Phosphatidylcholine-to-Triacylglycerol Pathway - Meï, Coline E.; Cussac, Mathilde; Haslam, Richard P.; Beaudoin, Frédéric; Wong, Yung-Sing; Maréchal, Eric; Rébeillé, Fabrice (Frontiers in Plant Science, 2017)
Triacylglycerol (TAG) accumulation often occurs in growth limiting conditions such as nutrient deprivations. We analyzed and compared the lipid contents of Arabidopsis cells grown under two conditions that inhibited growth as a way to study interactions between membrane and storage lipids. In order to inhibit C1 metabolism, the first condition utilized methotrexate (MTX), a drug that inhibits methyl transfer reactions and potentially reduces Pi-choline synthesis, the polar head of phosphatidylcholine (PC). MTX-treated cells displayed a 10-15 fold increase in TAG compared to that found in control cells. This corresponded to a net increase of lipids as the total amount of membrane glycerolipids was minimally affected. Under this condition, PC homeostasis appeared tightly regulated and not strictly dependent on the rate of Pi-choline synthesis. The second condition we investigated involved nitrogen deprivation. Here, we observed a 40-fold increase of TAG. In these cells, the overall lipid content remained unchanged, but membrane lipids decreased by a factor of two suggesting a reduction of the membrane network and a rerouting of membrane lipids to storage lipids. Under all conditions, fatty acid (FA) analyses showed that the FA composition of TAG was comparable to that in PC, but different from that in acyl-CoA, suggesting that TAG accumulation involved PC-derived DAG moieties. In agreement, analyses by qPCR of genes coding for TAG synthesis showed a strong increase of non-specific phospholipase C (NPC) expressions, and experiments using labeled (fluorescent) PC indicated higher rates of PC-to-TAG conversion under both situations. These results highlight a role for NPC in plant cell oil production.